Iowa Birdline update, November 19, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of Iowa Birdline updates for November 19, 1991. The highlights for the update include sightings of a Snowy Owl, Pacific Loon, Black-legged Kittiwake and a White-winged Scoter. Also included are handwritten notes with sightings of a Western Grebe, Varied Thrush and a Northern Goshawk. Epson - sheet feed/flatbed